Visualization of red blood cells flowing through a PDMS microchannel with a microstenosis: an image analysis assessment - Monteiro, Fernando C. (2014)
The present study aims to assess the motion of red blood cells (RBCs) under both shear and extensional flow using an image based technique. For this purpose, a microchannel having a smooth contraction was used and the images were captured by a standard high-speed microscopy system. An image processing and analyzing method has been developed in the MATLAB environment, to track the RBCs motion. The keyhole model, tested in this study, proved to be a promising technique to track individual RBCs in microchannels.